Efektivitas Rom Pasif Terhadap Tonus Otot Pasien Post Opersi Fraktur Ektermitas : Evidence Based Case Report (Ebcr) - Rohmah, Nur Saily; Rivani, Dyah (CV RIFAINSTITUT, 2023)
Fractures or broken bones are incidents of trauma to the bones with various causes. This condition results in damage to the bone and surrounding tissue, complications can occur in the limb bones if there is a lack of mobilization. Actions that can be taken to prevent more severe complications are by doing ROM motion exercises to check the strength of muscle tone. to determine the effectiveness of passive ROM on muscle tone in post extremity fracture patients. This type of research is a case study research. The focus in this study was the application of passive ROM training on muscle tone in extremity fracture patients. Results: there is a change in muscle tone in patients with post-extremity fracture after passive ROM. there are changes in muscle tone in patients with post-fracture extremities after passive ROM. Passive ROM can provide benefits to increase muscle strength in post-fracture patients in the extremities.